Comparison of Fracture Location and Extent of Comminution in Isolated Scaphoid Fractures Versus Transscaphoid Fracture-Dislocations. (May 2020) - Suszynski, Thomas M.; Ben-Amotz, Oded; Kargel, Jennifer S.; Bass, Robert; Sammer, Douglas M.
Background: Isolated scaphoid fractures (ISFs) are common, whereas transscaphoid fracture-dislocations (TSFDs) are not. Scaphoid fracture location and the extent of comminution are factors that affect treatment and outcome. The purpose of this study is to compare the radiographic characteristics of ISFs with TSFDs associated with greater arc injury.Methods: This study is a retrospective review of all ISFs and TSFDs that presented to our institution during a 5-year period. Fracture location (along the long axis of the scaphoid) was calculated by dividing the distance from the proximal pole to the fracture by the entire length of the scaphoid. The extent of comminution was measured in millimeters along the mid-axis of the scaphoid and divided by the entire length of the scaphoid.Results: One-hundred thirty-eight scaphoid fractures in 137 patients were identified. One-hundred twelve fractures (81%) were ISFs, and 26 (19%) were associated with a TSFD. The mean fracture location was more proximal in TSFDs than in ISFs. However, fractures occurred in the distal third of the scaphoid in 12% of ISFs compared with 0% of TSFDs. Nine percent of ISFs demonstrated comminution as compared with 12% of TSFDs. Extent of comminution was 16% and 28% for ISFs and TSFDs, respectively.Conclusion: Scaphoid fractures associated with greater arc injuries are located more proximally and are more comminuted than ISFs, and distal pole fractures rarely occur in the setting of TSFDs. The increased incidence and extent of comminution in TSFDs may be suggestive of a higher energy injury mechanism.